Efficiency optimization of variable speed induction motor drive using online backpropagation - Mohamad Yatim, Abdul Halim; Utomo, W. M. (2006)
Development of an efficiency optimization control for variable speed drive system is important not only from the viewpoints of energy saving but also from the broad perspective of greenhouse emission. In this paper the designs of a back propagation based efficiency optimization control (BPEOC) for variable speed compressor induction motor drive is described. The controller is designed to generate signal voltage and frequency references simultaneously. This technique allows for control of both the speed and efficiency. In order to achieve a robust BPEOC from variation of motor parameters, an online learning algorithm is employed. Simulation of the BPEOC and laboratory experimental set up has been developed using TMS320C60 digital signal processor. The result demonstrated a significant increase in efficiency and an improvement in speed performance